Factors affecting fruit size and quality in citrus species - Tuwana, Sebenzile W.(Sebenzile Wilbert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1999.